Novel nanocrystalline PdNi alloy catalyst for methanol and ethanol electro-oxidation in alkaline media - Qi, Zhen; Geng, Haoran; Wang, Xiaoguang; Zhao, Changchun; Ji, Hong; Zhang, Chi; Xu, Junling; Zhang, Zhonghua (Journal of power sources, 2011)
► Nanocrystalline PdNi alloy can be fabricated by dealloying Al 75Pd 10Ni 15 precursor. ► PdNi alloy shows an enhanced catalytic activity towards alcohol electro-oxidation. ► The enhanced performance can be attributed to the alloying of Pd with Ni. Nanocrystalline Pd 40Ni 60 alloy catalyst has been fabricated by dealloying a ternary Al 75Pd 10Ni 15 alloy in a 20 wt.% NaOH aqueous solution under free corrosion conditions. The microstructure and catalytic performance of the catalyst have been characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, high-resolution transmission electron microscopy, and cyclic voltammetry. The Pd 40Ni 60 alloy consists of nanocrystals with sizes of 5–10 nm, and Pd/Ni elements exist in a solid solution form. Moreover, nanocrystalline zones, amorphous zones and lattice distortion can be observed in the Pd 40Ni 60 alloy. Electrochemical measurements demonstrate that, for equivalent mass Pd, Pd 40Ni 60 has an enhanced electrocatalytic performance towards methanol and ethanol oxidation in alkaline media than nanoporous Pd. The nanocrystalline Pd 40Ni 60 alloy is a promising catalyst towards alcohol oxidation in alkaline media for fuel cell applications.